Pendampingan Digital Marketing Sebagai Strategi Pemasaran Usaha Budidaya Lele - Khusnul Rofida Novianti; Kenny Roz; Chalimatuz Sa'diyah (Badan Penerbitan Universitas Widyagama Malang, 2021)
Since 2018, the Indonesian government through the Ministry of Maritime Affairs and Fisheries has encouraged people to increase fish consumption through the Fish Eating Community Movement (GEMARIKAN) program. One of the popular fisheries commodities and has high nutritional value is catfish. Unfortunately, the catfish farming business is not widely known and uses technology and good marketing strategies. For this reason, assistance is needed regarding digital marketing in the catfish cultivation business in Mulyoagung Village, Dau District, Malang Regency. The implementation of this activity is carried out in a combination of online and offline, creating Google My Business, as well as using digital marketing in the catfish cultivation business. The results of this activity are brands, Google My Business links, and several social media platforms that are used as marketing strategies whose development will continue to be monitored regularly